Antarctic-Scale Ice Flow Lines Map Generation and Basin Delineation - Ze Yang; Zhizhong Kang (Remote Sensing, 2022)
Ice flow lines are the most dominant feature of ice sheet surfaces. Accurate delineation of basins is a prerequisite for mass balance. We therefore propose a new weight balance-based approach to extract the present most comprehensive ice flow lines and then re-delineate the Antarctic basin on this basis. In our approach, we define three impact factors to represent directional accuracy, smoothness, and physical character. Following this, a weight balance-based method is proposed, in which those factors are integrated via weights, to determine the pointing pixels (points or subpixels of the ice flow line). After that, the ice flow lines are continuously tracked. Finally, Antarctic basins were re-delineated based on it. The results indicate that the derived ice flow lines exhibit a rational ice flow pattern against the DEM and the proposed method remarkably improves the performance of results. Furthermore, compared with the Antarctic IMBIE (Ice sheet Mass Balance Inter-Comparison Exercise) basins, the redivided basins exhibit slight diversity, with differences in area and length of less than 11% and a directional accuracy of less than 1° (covering more than 90% of area). As a result, the redivided basins are beneficial to the investigation of the in-depth mechanism of ice shelf calving and mass balance in the Antarctic.